Identificação por decomposição de sinais de consumo de energia elétrica - (:unkn) unknown (Universidade Federal do Amazonas, 2016)
The identification by decomposition of electricity consumption signals tech- nique, we estimate the consumption of devices that form a power consumption signal. This technique, that can be called disaggregation or nonintrusive load monitoring, is important because it makes possible obtain information about the individual energy consumption of devices, allowing other approaches like power management, use in smart grids and Internet of Things (IoT). Energy disaggregation problem can be approached through dictionaries techniques, which summarize the most significant characteristics of the signals involved to signal disaggregation. In our proposal, we highlight two contributions. In the first, we modify the steady-state identi- fication (SSI) algorithm to deal with signals with variable dimensions and, then, we conducted a parameter analysis that changes the dictionaries and consequently produces different performances of disaggregation. Second, we propose a disaggrega- tion methodology using principal component analysis (PCA). The experiments were made using REDD database [1] and they demonstrate that the proposal produces results with higher accuracy when compared with other techniques.
Keywords: Análise de parâmetros; Análise de componentes principais; Análise singular espectral; Parameter analysis; Principal component analysis; Singular spectrum analysis; ENGENHARIAS: ENGENHARIA ELÉTRICA